Relationship of alcohol intake and sex steroid concentrations in blood in pre- and post-menopausal women: The European Prospective Investigation into Cancer and Nutrition - Rinaldi, S; Peeters, P; Bezemer, I; Dossus, L; Biessy, C; Sacerdote, C; Berrino, F; Panico, S; Palli, D; Tumino, R; Khaw, K; Bingham, S; et al. (2006)
Objective: Women with a moderate intake of alcohol have higher concentrations of sex steroids in serum, and higher risk of developing breast cancer, compared to non-drinkers. In the present study, we investigate the relationships between alcohol consumption and serum levels of sex steroids and sex-hormone binding globulin (SHBG) in 790 pre- and 1,291 post-menopausal women, who were part of the European Prospective Investigation into Cancer and Nutrition (EPIC). Methods: Serum levels of testosterone (T), androstenedione (Δ4), dehydroepiandrosterone sulphate (DHEAS), estrone (E 1), estradiol (E2) and SHBG were measured by direct immunoassays. Free T (fT) and free E2 (fE2) were calculated according to mass action laws. Current alcohol intake exposure to alcohol was assessed from dietary questionnaires. Results: Pre-menopausal women who consumed more than 25 g/day of alcohol had about 30% higher DHEAS, T and fT, 20% higher Δ4 and about 40% higher E1, concentrations compared to women who were non-consumers. E2, fE 2 and SHBG concentrations showed no association with current alcohol intake. In post-menopausal women, DHEAS, fT, T, Δ4, and E 1 concentrations were between 10% and 20% higher in women who consumed more than 25 g/day of alcohol compared to non-consumers. E2 or fE2 were not associated with alcohol intake at all. SHBG levels were about 15% lower in alcohol consumers compared to non-consumers. Conclusion: This study supports the hypothesis of an influence of alcohol intake on sex hormone concentrations in blood. © Springer Science+Business Media B.V. 2006.